Out of character: the impact of egalitarianism on a conservatives’ choice to purchase fair-trade products - Wong, Rachel Mei Ming (2024)
Although past literature has established the significance of the fair-trade movement to the pursuit of social equity for underdeveloped producers, consumers remain reluctant to patronise products marketed as fair-trade. Here, this behaviour is investigated using a more nuanced approach, one that combines the ‘knowns’ about consumer behaviour (e.g., tendency to avoid costs), with psychological insights grounded in the ideological factors that may underpin readiness to patronize fair-trade products based on the social equity goals of such products. Specifically, in the current literature, it is not clear to what extent political ideology, egalitarianism, and meritocracy might play a role in people’s ethical consumption decision- making process. These factors may influence patronage intentions, given the connection between fair-trade products and social equity. But limited research has systematically unpacked this possibility. This thesis’ research attempts to fill this void by examining the role that political affiliation and ideological leanings (e.g., egalitarianism), could play in shaping patronage of fair-trade products (or otherwise engaging in ethical consumerism).